Safety and immunogenicity of the DTP/HB /Hib combination vaccine: phase I study - Kusnandi Rusmil; Eddy Fadlyana; Novilia Sjafri Bachtiar; Hadyana Hadyana (Paediatrica Indonesiana, 2013)
Background The World Health Organization (WHO) hasrecommended the introduction ofhepatitis B (HB) and Haemophilusinfluenza type b (Hib) vaccines into routine childhood vaccinationprograms. A new diptheria/tetanus/pertussis (DTP) /hepatitis B/Hibpentavalent combination vaccine has been developed.Objective To evaluate the safety and immunogenicity of a newcombination DTP/HB/Hib liquid vaccin e in infants.Met hods An open-label, uncontrolled, prospective interventionphase I study was con ducted on 30 healthy infants aged 6- 11weeks. Each subject received 3 doses of DTP/HB/Hib vaccine,formulated by Bio Fanna, 0.5 mL intramuscularly at the leftanterolateral thigh region using a 25-gauge n eedle of 25 mmlength . Subjects were followed for 1 month after administration ofeach vaccine dose to evaluate its safety, while serum anti-diphteria,tetanus, HB, Hib, and per tussis antibodies were measured priorto the l '' dose and 1 month after the Jtd dose.Results Among 30 vaccinated subjects, 18 infants had fever within24 hours after the first vaccination. Most cases of fever were mildin intensity and resolved within 24 hours. No other systemic orlocal reactions, or serious adverse events were observed in oursubjects during the study. The immunogenicity results after Jtdvaccine dose showed that the geometric mean titer of the antipolyribosylribitolphosphate (PRP) antibody levels increasedsignificantly from 0.0041Î¼,g/mL to 4.3 7 Î¼,g/mL after vaccination,and most infants h ad a fourfo ld or greater rise in antibody levelsover their pre-injection levels . All subjects who received DTP/HB/Hib liquid vaccine had seropro tective antibodies againsttetanus, diphtheria,a and hepatitis B, while 29/30 infants hadseroprotective antibodies against pertussis.Conclusion This new diphtheria/tetanus/pertusis/hepatitis B/Hibcombination vaccine has excellent safety profile and antibodyresponses in infants. These results encourage further clinicalevaluation in phase II.